Patient, Clinician, and Healthcare Perspectives in Evaluating Care Pathways for Stable Chest Pain. Issue 3 (22nd April 2021) - Kwok, Chun Shing; Duckett, Simon; Satchithananda, Duwarakan; Potluri, Rahul; Morgan-Smith, Dot; Bellenger, Nick; Gunning, Mark; Mallen, Christian
Abstract : Chest pain is one of the most common reasons for patients to present to healthcare professionals. One of the main challenges with the management of chest pain is the wide differential diagnosis, ranging from minor chest trauma to potentially life-threatening acute myocardial infarction. In a patient-centered health service pathway, the aim is to assess, investigate, diagnose, and treat patients in the safest and most accurate, time, and cost-efficient manner. This report describes the concept of clinical pathways and their importance. It iterates different perspectives of the investigation of chest pain and the barriers to understanding the clinical sequence of events. By considering the patient, clinician, and healthcare service perspective, it is possible to critically evaluate the current stable chest pain pathway. This exercise gives consideration into the way in which patient care could be improved.